FRI0309 SEVERE ABDOMINAL MANIFESTATIONS IN JUVENILE DERMATOMYOSITIS. (June 2019) - Besnard, Caroline; Gitiaux, Cyril; Girard, Muriel; Galmiche-Rolland, Louise; Talbotec, Cécile; Quartier, Pierre; Berteloot, Laureline; Bodemer, Christine; Bader-Meunier, Brigitte
Abstract : Background: Juvenile dermatomyositis (JDM) is a rare and heterogeneous children-onset idiopathic inflammatory myopathy. It primarily affects skeletal muscle and skin, but also pulmonary, cardiac and gastrointestinal systems in a subset of patients. Gastrointestinal (GI) involvement occurs in 22 to 37% of JDM patients and have been described only in a few case reports. Objectives: To describe causes of severe abdominal manifestations in JDM patients. Methods: Retrospective monocentric study. Inclusion criteria were (i) diagnosis of JDM according to the modified Bohan and Peter criteria before 16 years of age, (ii) occurrence of severe involvement of any intra-abdominal organ, (iii) follow-up at Necker Hospital from 2005 to 2018. Severe abdominal manifestation was defined as a potential life-threatening abdominal organ event, need for abdominal surgery and/or parenteral nutrition. Gastrointestinal (GI) involvement was defined by severe abdominal pain, dysphagia, digestive hemorrhage, obstruction, ulceration and/or perforation. Severe hepatitis was defined by an elevation of liver enzymes exceeding five times the upper limit associated with an elevation of γ-glutamyl transferase (γGT) activity and/or liver failure. Abdominal manifestations were classified as certain or probable primary JDM involvement, therapy-related event or infection-related event. Results: Nine patients with 19 abdominal complications were identified among 110 JDM patients followed during the study period (8, 3%). Diagnosis of JDM was made at a median age of 10.7 years-old [range, 3.7 – 14.4], with a median CMAS of 7 [range, 2 – 48], median MMT of 47 [range, 38 – 76], a median creatine kinase level of 3 812 UI/L [range, 170 – 14 054], and a median follow-up of 3 years [range, 0.4 – 6.3]. Seven patients were positive for either anti-NXP2 (n = 4), anti-TIF1-γ (n = 2) or anti-MDA5 (n = 1) antibodies. JDM-related abdominal disease comprised GI involvement (n = 10), acute pancreatitis (n = 4) and hepatitis (n = 3). The revealing symptom for GI involvement and acute pancreatitis was abdominal pain. Five patients with severe abdominal pain, vomiting and/or obstruction, underwent abdominal imaging revealing thickening of colon (n = 2) and/or ileum mucosa (n = 2). Hepatitis was found in 3 patients with an uncommon extensive steatosis with moderate inflammation and perisinusoidal fibrosis (n = 2). Treatment-related complications were considered certain for methotrexate-induced liver toxicity (1 patient) and possible for duodenal perforations (1 patient) 3 days after a methylprednisolone pulse. At last visit, JDM was clinically inactive in four patients. Three patients died from refractory JDM, 2.9 years [range, 2 – 3.6] after the JDM diagnosis, among the 9 patients identified in this study versus only 1/92 of the other JDM patients from our cohort. Conclusion: Primary JDM involvement was the main cause of severe abdominal manifestations and associated to a high mortality rate. We highlight for the first time that pancreatitis should be considered as a main diagnosis in JDM patients who develop severe and/or sustained abdominal pain. Disclosure of Interests: Caroline Besnard: None declared, cyril gitiaux: None declared, Muriel Girard: None declared, Louise Galmiche-Rolland: None declared, Cécile Talbotec: None declared, Pierre Quartier Consultant for: AbbVie, Chugai-Roche, lilly, Novartis, Novimmune, Sanofi, and SOBI, Consultant for: AbbVie, Chugai-Roche, Lilly, Novartis, Novimmune, Sanofi, and SOBI, Speakers bureau: AbbVie, BMS, Chugai-Roche, Novartis, Pfizer, and SOBI, Speakers bureau: AbbVie, BMS, Chugai-Roche, Novartis, Pfizer, and SOBI, Laureline Berteloot: None declared, christine bodemer: None declared, Brigitte Bader-Meunier: None declared